FRI0632 ASSOCIATION BETWEEN ULTRASOUND DIAGNOSIS AND ANALYTICAL AND SEROLOGICAL DATA IN PATIENTS WITH SUSPECTED PRIMARY SJöGREN SYNDROME. (June 2019) - Nogal, Laura Barrio; Bohórquez, Cristina; Ruiz, Lucía; Abbasi, Adrián; Gómez, Ana Pérez; Movasat, Atusa; Atrio, Ana Sánchez; Albarrán, Fernando; Cuende, Eduardo; Pretel, Paula; Emperiale, Valentina; Mon, Melchor Álvarez de
Abstract : Background: Pathophysiology of primary Sjögren syndrome (SSp) is characterized by oligoclonal B-cell proliferation and ectopic lymphoid tissue formation. The association between ultrasound glandular parenchyma heterogeneity and hyperproduction of autoantibodies, which in turn represents characteristic B-cell hyperactivity of SSp, is described. Objectives: To study the association between major salivary gland ultrasound (MSGUS) and their respective pathological grades with the analytical and serological data, and activity indexes obtained in patients with suspected SSp. Methods: 72 patients were recruited consecutively with clinical and/or analytical suspicion of SSp from the Rheumatology outpatient consultations at the Príncipe de Asturias Hospital (2015-2018). Demographic, serological and validated activity indexes, ESSPRI and ESDAI, were collected. All of them underwent a MSGUS and their results were classified in three grades according to the Cornec et al system : normal (grade 0 and 1), mild (grade 2) and moderate-severe (grades 3 and 4). The final SSp diagnosis was made using both 2002 AECG and 2016 ACR/EULAR classification criteria. Data were analyzed using the software STATA. Association between MSGUS and qualitative variables was described according to the number of cases and the percentage by grades of MSGUS; the significance of the associations was tested with the Chi square test. As for the quantitative variables, the association was described with median and interval interquartile (IIQ) by grades of MSGUS and the significance of the association was verified with the non-parametric test of Kruskall-Wallis. Results: From patients with pathological MSGUS: 51% had antiRo52, 51% antiRo60 and 36% anti-La positive; 62% hypergammaglobulinemia, 40% positive rheumatoid factor (RF), 6% and 13% C3 and C4 hypocomplementemia, respectively. Mean values were obtained: ESR 36, CRP 1.6, RF 12, ESSPRI 5.6 and ESSDAI 2. Statistically significant differences (p<0.05) were only found in antiRo52 and hypergammaglobulinemia variables in patients with normal MSGUS exam compared to those with mild and moderate-severe pathological MSGUS exam. These data suggest that there could be differences for antiRo60, AntiLa and ESSPRI variables eventhough statistical significance was not achieved (p>0.150 in all associations explored). No differences have been found for RF, C3 and C4 hypocomplementemia, ESR, CRP and ESSDAI variables (table1 ) . Conclusion: In this series of patients, a statistically significant association was found between the positivity of anti-Ro antibodies, hypergammaglobulinemia and MSGUS, as well as its subdivision by pathological grades. No statistical significant association was found between MSGUS and positivity of antiRo60 and antiLa antibodies and ESSPRI, probably due to the small sample size. There were no differences for the rest of the variables analyzed (RF, complement, acute phase reactants and ESSDAI). References: [1] Ultrasonography of salivary glands-a highly specific imaging procedure for diagnosis of Sjögren's syndrome Dirk Wernicke J Rheumatol. 2008Feb;35(2):285-93. Epub 2008 Jan 15 [2] .The usefulness of ultrasound in the diagnostics of Sjögren's syndrome. Fadhil Saied J Ultrason. 2013 Jun;13(53):202-11. Disclosure of Interests: None declared